Effects of ten biofeedback sessions on athletes` physiological, psychological, and cognitive functioning: A randomized controlled trial with international tennis players - Makaraci, M.; Makaraci, Y.; Zorba, E.; Lautenbach, F. (Perceptual and Motor Skills, 2024)
Our aim in this study was to test the effect of 10 sessions of biofeedback (BFB) on physiological, psychological, and cognitive functioning of international tennis players. In this randomized controlled trial, we recruited 16 international tennis players (11 male, 5 female; Mage = 17.31, SD = 0.87 years), who were randomly assigned to either an intervention group (IG; n = 8) or a control group (CG; n = 8). Those in the IG received 10 multimodal BFB sessions over four weeks, while those in the CG received no intervention. We assessed physiological, psychological, and cognitive parameters before and after the intervention and found a positive effect for skin temperature, state anxiety, and cognitive performance in the IG versus the CG. We provide preliminary data that 10 sessions of multimodal BFB improved cognitive functions and reduced anxiety symptoms in international tennis players. Future investigators should consider increasing sample size, incorporating an active CG, and studying these effects across diverse athletic disciplines.